Using Ultrasound and Power-Assisted Devices through Lateral Incision: The OCCULT Technique for Gynecomastia—A Multicentric Large Series Study - Gupta, Rajat; Bansal, Priya; Chugh, Anmol; Shah, Saumil Girish; Chaudhary, Gautam (Indian Journal of Plastic Surgery, 2025)
Gynecomastia is a common condition characterized by male breast enlargement, which can have a profound psychological impact on affected individuals. Surgical intervention is often sought to alleviate these concerns. This study evaluates the lateral port technique for gynecomastia surgery, which combines power-assisted liposuction (PAL) and ultrasound-assisted liposuction (UAL) to achieve optimal surgical outcomes with no scar on front of chest.A retrospective analysis was conducted on 967 patients who underwent gynecomastia surgery using the Out of Sight, No Cut on Front of Chest Using Ultrasound and Power-Assisted Devices through Lateral Incision (OCCULT) technique between January 2022 and December 2023. The procedures were performed at multiple centers located in New Delhi, Gurugram, and Mumbai, India. This technique involves a single lateral chest wall incision and incorporates both PAL and UAL to ensure effective tissue removal and contouring. Outcomes assessed included surgical efficacy, complication rates, and patient satisfaction. The surgeries were performed by a team of experienced surgeons, ensuring the reproducibility and consistency of the method.The OCCULT technique demonstrated high efficacy and high patient satisfaction. Among the 967 patients, 93.3% reported being satisfied with the surgical results. Excellent scar quality was reported by 97.1% of the patients. Moreover, the scar was out of sight, that is, no scar on the front of chest was made in the OCCULT technique for gynecomastia surgery. Complications were minimal, with only 0.8% experiencing seroma formation and no cases of necrosis observed.The OCCULT technique for gynecomastia surgery is an effective and reproducible method that provides aesthetically favorable results with minimal complications. Its ability to address the psychological and physical burdens of gynecomastia highlights its value in modern surgical practice.
Keywords: gynecomastia; power-assisted liposuction; ultrasound-assisted liposuction; pull-through technique; surgical outcomes